2001
DOI: 10.1051/vetres:2001140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HMB (?-hydroxy-?-methylbutyrate) on antibody secreting cells (ASC) after in vitro and in vivo immunization with the anti-Yersinia ruckeri vaccine of rainbow trout (Oncorhynchus mykiss)

Abstract: -In practice, protection of fish against disease by immunization is of limited effectiveness. Therefore, research is concentrated on how to improve the potency and efficacy of vaccines and how to optimally activate the cell-mediated immunity and the specific antibody response. In the present study, the influence of HMB (β-Hydroxy-β-methylbutyrate) on the antibody secreting cells (ASC) after both in vitro and in vivo immunization of rainbow trout (Oncorhynchus mykiss) with the anti-Yersiniose vaccine was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The results of this part of the study are evidence that HMB in the diet had an immunostimulating influence on phagocyte and lymphocyte activity in pikeperch. Similar immunomodulating effects of HMB on nonspecific cellular defence mechanisms in rainbow trout have been observed in our previous studies (Siwicki et al 2001, 2003). These studies strongly suggested that supplemental HMB acts as an immunomodulator, and that at doses between 10 and 50 mg kg −1 of the feed it stimulated phagocyte activity examined through the phagocytic ability and potential killing activity, and lymphocyte activity analysed through the proliferative response induced by mitogens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this part of the study are evidence that HMB in the diet had an immunostimulating influence on phagocyte and lymphocyte activity in pikeperch. Similar immunomodulating effects of HMB on nonspecific cellular defence mechanisms in rainbow trout have been observed in our previous studies (Siwicki et al 2001, 2003). These studies strongly suggested that supplemental HMB acts as an immunomodulator, and that at doses between 10 and 50 mg kg −1 of the feed it stimulated phagocyte activity examined through the phagocytic ability and potential killing activity, and lymphocyte activity analysed through the proliferative response induced by mitogens.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, Siwicki and colleagues, in cooperation with Department of Animal Sciences, Iowa State University, USA examined the role of leucine and leucine catabolites in the activity of nonspecific defence mechanisms in rainbow trout ( Oncorhynchus mykiss (Walbaum)). The results showed that HMB, applied in the diet, activated cellular and humoral defence mechanisms and provided protection against diseases in intensive rainbow trout culture (Siwicki, Morand, Fuller, Nissen, Kazun & Glompski 2001; Siwicki, Morand, Fuller, Nissen, Goryczko, Ostaszewski, Kazun & Glompski 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Leucocyte phagocytosis is an important reaction activated in Y. ruckeri ‐vaccinated fish as well as antibody production (Cossarini‐Dunier 1986) and lymphocyte proliferation (Siwicki & Dunier 1993; Siwicki, Morand, Fuller, Nissen, Kazun & Glombski 2001). Enzyme‐linked immunosorbent assays (ELISA) have been developed for the detection of many fish pathogens.…”
Section: The Diseasementioning
confidence: 99%
“…Several promising adjuvants, natural and synthetic drugs and biological modifiers have been tested in fish in vivo and in vitro. The substances, such as chitosan, β-glucan, muramyl dipeptide, trace mineral and vitamin combinations as well as various products derived from plants and animals, are effective in stimulating or modulating non-specific defence mechanism, and offer protection against viral and bacterial diseases in fish (Siwicki et al 1994;Siwicki et al 2001;Kodama et al 1993;Mulero et al 1998a;Cuesta et al 2002a).…”
mentioning
confidence: 99%